Implementation of Islamic Education Values Based on Prophetic Communication in Forming Akhlakul Karimah in Madrasah Tsanawiyah - M. Jaedi ,; Imam Hambali,; Muslih Hidayat,; Sofwan,; Zaki Faddad Syarif Zain,; Eko Purnomo, (TADRIS: Jurnal Pendidikan Islam, 2025)
This research aims to determine the implementation of Islamic education values based on prophetic communication in forming akhlakul karimah at MTs Darul Ulumissyar'iyyah Telang Karya in producing quality students. The research methods used are observation, interviews, and documentation. Data analysis techniques include data condensation, data presentation, and conclusions. The research results obtained show that efforts to produce quality students are implemented to be able to create students with a spirit of humanization (amar ma'ruf), liberation (nahi munkar), and transcendence (tu'minu billah). The implications of implementing Islamic education values based on prophetic communication at MTs Darul Ulumissyar'iyyah Telang Karya include (a) humanization: mutual respect, tolerance, social care, love of the country, compassion, respect for differences, mutual help among others; (b) liberation: high learning motivation; (c) transcendence: discipline, having responsibility in matters of worship.